Analgesic Effect of Zanthoxylum nitidum Extract in Inflammatory Pain Models Through Targeting of ERK and NF-κB Signaling - Qin, Fenfen; Zhang, Han; Liu, Anlong; Wang, Qisheng; Sun, Qinmei; Lu, Shengfeng; Li, Qian; Guo, Hongwei; Liu, Xing; Lu, Zhigang (Frontiers in Pharmacology, 2019)
Background Zanthoxylum nitidum (Roxb.) DC., also named Liang Mianzhen (LMZ), one kind of Chinese herb characterized with anti-inflammatory and relieving pain potency, which is widely used to treat injuries, rheumatism, arthralgia, stomach pain and so on in China. But its mechanism related to the anti-hyperalgesic has not been reported. The aim of this study was to investigate the analgesic activity of Liang Mianzhen on mice with Complete Freund adjuvant (CFA)-induced chronic inflammatory pain. Meanwhile, the peripheral and central mechanisms of analgesic effect of Liang Mianzhen were further examined via observing the effects of Liang Mianzhen on the signal pathway associated with inflammatory induced hyperalgesia. Methods The inflammatory pain model was established by intraplantar injection of CFA in C57BL/6J mice. After 1 day of CFA injection, the mice were treated with LMZ (100 mg/kg) for seven consecutive days, and the behavioral tests were measured after the daily intragastric administration of LMZ. The morphological changes on inflamed paw sections were determined by hematoxylin eosin (HE) staining. Changes in the mRNA expression levels of tumor necrosis factor (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β) and nuclear factor κB p65 (NF-κBp65) were measured on day seven after CFA injection by using real-time quantitative PCR analysis and enzyme linked immunosorbent assay (ELISA) method, respectively. Moreover, immunohistochemistry and western blotting were used to detect extracellular regulated protein kinases 1/2 (ERK1/2) and NF-κB signal pathway activation. Results The extract of LMZ (100 mg/kg) showed a significant anti-inflammatory and analgesic effect in the mice model. The paw edema volume was significantly reduced after the administration of LMZ compared to CFA group, as well as the paw tissues inflammatory damage was relived and the numbers of neutrophils in mice was reduced significantly. The CFA-induced mechanical threshold and thermal hyperalgesia value were significant improved with LMZ treatment at day three to day seven. We also found the mRNA levels of TNF-α, IL-1β, IL-6 and NF-κBp65 were down-regulate after 7 days from the LMZ treatment compared to CFA group. Meanwhile, LMZ significantly suppressed over-expression of the phosphorylation of ERK1/2 and NF-κBp65 in peripheral and central. Conclusion The present study suggests that the extract of LMZ attenuates CFA-induced inflammatory pain by suppressing the ERK1/2 and NF-κB signaling pathway at both peripheral and central level.